2009
DOI: 10.1177/1933719109335068
|View full text |Cite
|
Sign up to set email alerts
|

Placental and Fetal Hemodynamics After Labetalol or Pindolol in a Sheep Model of Increased Placental Vascular Resistance and Maternal Hypertension

Abstract: We investigated the effects of labetalol and pindolol on uterine, placental, and fetal hemodynamics following norepinephrine-induced maternal hypertension in a sheep model of increased placental vascular resistance. Also, we examined fetal and placental hemodynamic responses to acute hypoxemia after antihypertensive medication. Norepinephrine increased maternal heart rate (HR), mean arterial pressure (MAP) and uterine vascular resistance (R(UtA)), and decreased uterine volume blood flow (Q(UtA)). Both labetalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…33 These findings are consistent with both Doppler ultrasound studies, which showed that α-methyldopa does not affect uteroplacental or fetal hemodynamics 33,34 and a sheep model of maternal hypertension in which labetalol and pindolol (another nonselective β-blocker) compromised uteroplacental perfusion. 35 Beta-blockers also may affect urethral development by interfering with Leydig cell activity in the testis. Leydig cells begin production of testosterone by week 8 and influence sexual differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…33 These findings are consistent with both Doppler ultrasound studies, which showed that α-methyldopa does not affect uteroplacental or fetal hemodynamics 33,34 and a sheep model of maternal hypertension in which labetalol and pindolol (another nonselective β-blocker) compromised uteroplacental perfusion. 35 Beta-blockers also may affect urethral development by interfering with Leydig cell activity in the testis. Leydig cells begin production of testosterone by week 8 and influence sexual differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sympathetic activation in the pregnant dam may alter several physiological parameters that might affect the fetus. For example, sympathetic activation may increase maternal heart rate and blood pressure, which in turn may influence the blood flow to the placenta ( Erkinaro et al., 2009 ). Furthermore, the uterus contains alpha-adrenergic receptors, and stimulation of these receptors has been shown to increase both uterine blood flow and uterine contractility ( Sato et al., 1996 ).…”
Section: Potential Mechanisms Underlying the Pns Phenotypementioning
confidence: 99%
“…Alternatively, despite its ß1 cardio-selective nature 53 , bisoprolol could have a direct effect on the placental vasculature. This is supported by evidence of ß1 receptors 54 , 55 in placental vasculature and placental vasoconstriction seen following exposure to ß blockers in vitro 56 , 57 . The potential negative effect of antenatal ß blocker use on fetal growth has long been considered 51 , 58 – 61 .…”
Section: Discussionmentioning
confidence: 73%